Eksistensi Terminal Waramosio dalam Meningkatkan Kesejahteraan Masyarakat Setempat (Ditinjau dari Pendekatan Sosiologi) - Asis, Patta Hindi; Mattalitti, Muhammad Ihsan; Attamimi, Ulfah; Puspitafuri, Cindy; Susanti, Neni; Satyadharma, Maudhy (DIALEKTIKA: Jurnal Ekonomi dan Ilmu Sosial, 2024)
Today's passenger terminal is starting to erode its existence with various problems plaguing it. This research was conducted to examine the existence of the Waramosio Terminal in improving the welfare of the local community in terms of a sociological approach and to analyze the efforts that must be made to optimize the terminal's function by the Southeast Sulawesi Provincial Transportation Service. The method used is a descriptive qualitative method by conducting interviews with ten informants. The theory used is Coleman's Rational Choice theory. The results found are that the existence of the Waramosio Terminal today is increasingly eroded and its function is decreasing. This needs to be paid attention to and efforts made by the Southeast Sulawesi Provincial Transportation Service to optimize the terminal's function and its existence in the community.